2016
DOI: 10.4103/1319-3767.173762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of telmisartan on histological activity and fibrosis of non-alcoholic steatohepatitis: A 1-year randomized control trial

Abstract: Background/Aim:Telmisartan can attenuate two hit pathogenesis of non-alcoholic steatohepatitis (NASH). This study aimed to observe the effect of Telmisartan on non-alcoholic fatty liver disease (NAFLD) activity score (NAS) and fibrosis score in NASH patients.Patients and Methods:A total of 50 NASH patients were randomized; 35 of group 1 were treated with Telmisartan 40/80 mg once daily with life style modification (TL) and 15 of group 2 underwent only life style modification (L) for 1 year. At the end, 20 of T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 28 publications
1
27
0
1
Order By: Relevance
“… 27 However, GGT was previously described as a better baseline and dynamic marker of histological changes than ALT and AST in NASH. 28 , 29 It is plausible that sitagliptin improved HOMA IR and fasting blood sugar in this study, in accordance with previous studies. 12 …”
Section: Discussionsupporting
confidence: 92%
“… 27 However, GGT was previously described as a better baseline and dynamic marker of histological changes than ALT and AST in NASH. 28 , 29 It is plausible that sitagliptin improved HOMA IR and fasting blood sugar in this study, in accordance with previous studies. 12 …”
Section: Discussionsupporting
confidence: 92%
“…Telmisartan, valsartan and olmesartan were also used in other studies, with treatment durations ranging from two to 12 months. The study by Alam et al [ 22 ] recommended lifestyle modification for all participants. Patients in the study by Torres et al [ 20 ] were administered an equal dose of rosiglitazone, whereas a placebo was used in the study by McPherson et al [ 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…These results are consistent with a clinical study that reported significantly improved NAFLD and fibrosis scores for telmisartan plus lifestyle modifications relative to lifestyle modifications alone in human patients with NASH. 57 Differential effects of pacritinib and telmisartan in the STAM model likely reflect the additional mechanism of action, PPARγ partial agonism, associated with telmisartan. This has effects on hepatic fatty oxidation, hepatic lipogenesis, and peripheral as well as hepatic insulin sensitivity.…”
Section: Discussionmentioning
confidence: 99%